ProgRef v3:Computer system to obtain data in schedules of reinforcement with humans - additional resources (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
The objective of this article was to describe some additional resources in the software ProgRef v3 (Costa and Banaco, 2002). In the article are characterized the "Shaping", "Training", "Open recorded session" and "Record parameters of the session" resources. The article also presents one file of the MS-Excel® that contains a macro which realizes the analyses of data from files of the interresponses time (IRTs). The additional resources presented here attempt to facilitate the researcher's work (i.e., the record and use of the parameters of one experimental session and the file with a macro) as well as to offer resources for acquisition of the studied operant response (i.e., shaping and training).